Bilateral Panuveitis in a Patient on Vemurafenib BRAF Inhibitor Therapy for Stage IV Melanoma. Issue 4 (July 2014) - Agemy, Steven A.; Mehta, Ankur N.; Pachydaki, Sophia I.; Tewari, Asheesh
Purpose: To describe a case of recurrent, bilateral panuveitis caused by the BRAF proto-oncogene inhibitor vemurafenib. Methods: Case report. Results: A 25-year-old woman developed bilateral panuveitis and macular edema after initiating treatment with the BRAF enzyme inhibitor vemurafenib for stage IV cutaneous melanoma. The patient was successfully treated with sub-Tenon triamcinolone injections along with cessation of the medication. Conclusions: Panuveitis is a potential adverse effect of vemurafenib. Good communication with oncology is necessary, in case the medication needs to be discontinued.